Innovation in research: the challenge and activities in progress/ L'innovazione nella ricerca: la sfida e l'attività in corso - DE PAOLI, ORIO; MONTACCHINI, ELENA PIERA (Scuole di dottorato, 2009)
The fourth edition of the Osdotta seminar, was held in Turin from 10-13 September 2008. The Seminar, set up as a moment of reflection about the tendencies that characterize the internal research of the Technology of Architecture, expanded its area of interest, opening up to different and wider horizons for new objectives of research. The program of the three days of meetings developed, as in the preceding editions, with an organic series of thematic tables merging in the final round table that hosted the discussions and the verification of the three external valuators.